Abnormal Ca2+ handling and reduced Ito contribute to citalopram-induced QT prolongation and cardiac arrhythmias - Li, Yangpeng; Xie, Jiamin; Zheng, Yuqing; Li, Jianhong; Zhao, Min; Liu, Li; Shen, Hongping; Lei, Ming; Tan, Xiaoqiu; Xiao, Juan; Liu, Xueru; Chen, Tangting (Frontiers in Pharmacology, 2025)
BackgroundCitalopram (CIT) is widely used as an anti-depressant and has been reported to be associated with QT interval prolongation and increased vulnerability of torsades de pointes (TdP), although the underlying mechanism remains unclear.ObjectiveThe aim of this study is to determine the proarrhythmic properties and underlying mechanisms of CIT.MethodsMice were intraperitoneally injected with CIT or saline (SAL) for 4 weeks. Echocardiograms and electrocardiograms were performed to evaluate the cardiac electrophysiological and hemodynamic properties. Proarrhythmic mechanisms of CIT were then explored using optical mapping. Finally, transcriptomic array, RT-qPCR, and whole-cell patch-clamp were conducted to explore and validate the potential ionic mechanisms of CIT-related electrical abnormalities.ResultsCIT treatment induced QT prolongation and increased the vulnerability of cardiac arrhythmias in the absence of structural or hemodynamic changes. Optical mapping showed that action potential duration (APD) and Ca2+ transient duration (CaTD) were prolonged, but the degree of prolongation was heterogeneous, resulting in impaired Vm–Ca2+ coupling in CIT-treated hearts. Meanwhile, CaT alternans exhibited a regional preference for initiating ventricular tachyarrhythmias in hearts treated with CIT. The transcriptomic array showed that multiple potassium channels were downregulated in hearts treated with CIT, which were confirmed by RT-qPCR. Prolonged APD and downregulated transient outward potassium current (Ito) and L-type calcium current (ICa-L) were recorded in isolated single cardiomyocytes with the patch-clamp technique after CIT treatment.ConclusionCIT treatment resulted in QT prolongation and higher susceptibility of ventricular arrhythmia. Regions with serious cardiac alternans were mainly responsible for initiation of CIT-related arrhythmias. Abnormal Ca2+ handling and decreased Ito-related gene expression likely underlie the ionic mechanism and may be a novel target for CIT-related arrhythmias.